2022
DOI: 10.3389/fpain.2022.893530
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Onset Opioids for Management of Breakthrough Cancer Pain: Considerations for Daily Practice

Abstract: Background and ObjectiveRapid-onset opioids (ROOs) are effective treatments for breakthrough cancer pain (BTcP) given their rapid onset of action and relatively short duration of analgesia. The aim of this article is to describe specific considerations for the use of ROOs in daily practice, focusing on dose titration and treatment of specific populations.Type of ReviewWe conducted a narrative review on the use of ROOs for BTcP. We selected papers according to the following search terms: “breakthrough cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Breakthrough pain in patients with head and neck cancers is characterized by a large number of episodes/day and the predictability, particularly with ingestion of food; thus, it is necessary to set up proper pain therapy based on drugs that meet the needs of patients and allows proper feeding ( 77 ), avoiding oral drugs and preferring transdermal drugs and nasal fentanyl preparations ( 78 ).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Breakthrough pain in patients with head and neck cancers is characterized by a large number of episodes/day and the predictability, particularly with ingestion of food; thus, it is necessary to set up proper pain therapy based on drugs that meet the needs of patients and allows proper feeding ( 77 ), avoiding oral drugs and preferring transdermal drugs and nasal fentanyl preparations ( 78 ).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Traditionally, scheduled long-acting opioids are used for background pain and short-acting immediate-release oral opioids are used on an “as needed” basis to treat breakthrough pain [ 13 , 23 , 24 , 25 ]. There are different types of short- and long-acting opioids, such as Morphine, Hydromorphone, Oxycodone, Methadone, Oxymorphone, and Transdermal and transmucosal Fentanyl, for scheduled and breakthrough pain [ 24 , 26 , 27 ]. In hospitalized cancer patients, the use and ratios of scheduled (SCH) and breakthrough pain or rescue (BTO) opioids have a very wide range [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are different types of short- and long-acting opioids, such as Morphine, Hydromorphone, Oxycodone, Methadone, Oxymorphone, and Transdermal and transmucosal Fentanyl, for scheduled and breakthrough pain [ 24 , 26 , 27 ]. In hospitalized cancer patients, the use and ratios of scheduled (SCH) and breakthrough pain or rescue (BTO) opioids have a very wide range [ 24 , 27 , 28 ]. Scheduled opioids have no ceiling effect and therefore no dosing limit may be required until they are associated with unmanageable side effects, like constipation, confusion, delirium.…”
Section: Introductionmentioning
confidence: 99%
“…Given the poor analgesic efficacy of morphine for unpredictable BTcP, rapid-onset opioids (ROOs) are recently considered to be the most suitable medication for "on-demand" treatment of BTcP in cancer patients [12]. Numerous clinical trials and meta-analysis have demonstrated the superior efficacy of transmucosal fentanyl formulations over opioids in counteracting BTcP [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%